The impact of COVID-19 pandemic on fertility behaviour in Indian states: Evidence from the National Family Health Survey (2019/21). - Md Mahfuzur Rahman; Manas Ranjan Pradhan; Manoj Kumer Ghosh; Md Moshfiqur Rahman (PLoS ONE)
Background The COVID-19 pandemic affected a broad spectrum of people's lives very quickly. Although the pandemic could influence people's fertility behaviours in several ways, there is little knowledge about such influence in diverse socioeconomic and cultural settings. This study investigated the impact of the COVID-19 pandemic on fertility behaviours and desires among women in a lower-middle-income country, India. Data and methods Our study analyzed cross-sectional data from 13 states and union territories (UTs) in India that were surveyed in pre- and post-lockdown periods by the 2019/21 National Family Health Survey (NFHS). The data were analysed using the descriptive analysis technique and the multilevel logit model. All these analyses were performed using the technique developed for complex sample design. Results The poverty-stricken states of Uttar Pradesh and Jharkhand and the Odisha state with moderate socioeconomic status experienced a significant decrease in contraceptive use and non-significant changes in the desire for birth and sexual activities after the lockdown. Contraceptive use significantly increased after the lockdown in the rich states of Punjab, Delhi, and Tamil Nadu, as well as in the Arunachal Pradesh state with moderate socioeconomic status. The changes in fertility behaviours in Uttar Pradesh, Jharkhand, and Odisha may influence fertility positively, while those changes in Punjab, Delhi, Tamil Nadu, and Arunachal Pradesh may influence fertility negatively. Conclusion At the aggregate level, there was a significant increase in desire for another child and a decrease in contraceptive use after the lockdown, which may influence fertility positively but can be compensated by reduced sexual activities. The influence of the fertility trends in the states with pro-natalist changes on India's recent fertility trend could be greater than those with anti-natalist changes, which can be better understood by analyzing reliable data from a couple of years following the 2019/21 NFHS.